Subtly manipulating the end group structures of DPP-centered dyes for the diverse aggregate fluorescence and stimuli-responsive behaviors. (June 2019) - Sun, Qikun; Zhang, Kai; Fan, Xiaojing; Tang, Liangliang; Liu, Linxi; Wang, Yanhui; Ding, Qi; Zhai, Min; Xue, Shanfeng; Yang, Wenjun
Abstract: Subtle modification on molecular structure can play a crucial role in determining solid-state fluorescence properties and stimuli-responsive behaviors. In the current work, we utilize the condensation reactivity of benzaldehyde attached at the periphery of 1, 4-diketopyrrolo[3, 4-c]pyrrole (DPP) with benzil and phenanthrene-9, 10-dione to design and synthesize two new DPP-centered A′‒A‒A′-type dyes (DPPBI and DPPPI), and they can be regarded as the analogues with and without the locked two peripheral phenyls. DPPBI and DPPPI show similar solution optical properties, however, their pristine solids emit bright yellow (570 nm) and near-infrared (NIR, 685 nm) fluorescence, respectively, indicating that the tiny structure change can induce a remarkable aggregate emission difference up to 115 nm. Moreover, when mechanically grinding the pristine solids, both ground states emit the red fluorescence with slightly different peak wavelengths of 615 nm for DPPBI and 623 nm for DPPPI, revealing that DPPBI and DPPPI are all mechanofluorochromice (MFC) dyes but exhibit the opposite MFC shift direction. These dichotomy emission and MFC behaviors are analyzed and discussed and demonstrate that subtle manipulation on molecular end groups can acquire unique aggregation emission and stimuli-responsive behaviors. Graphical abstract: Two new DPP-centered A'‒A‒A'-type dyes (DPPBI and DPPPI) are all mechanofluorochromice (MFC) materials but exhibit the opposite MFC shift direction. Image 1 Highlights: Two new DPP-centered A′‒A‒A′-type dyes (DPPBI and DPPPI) were designed and synthesized. DPPBI and DPPPI are all mechanofluorochromice (MFC) dyes but exhibit the opposite MFC shift direction. The as-synthesized DPPBI and DPPPI fluoresces yellow in solution but can aggregate into distinguishing yellow and NIR-emitting solids, respectively. Subtle manipulation on end groups can acquire unique aggregation emission and stimuli-responsive behaviors.